2021
DOI: 10.1101/2021.02.11.21251581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A genetically-informed study disentangling the relationships between tobacco smoking, cannabis use, alcohol consumption, substance use disorders and respiratory infections, including COVID-19

Abstract: Background Observational studies suggest smoking, cannabis use, alcohol consumption, cannabis use, and substance use disorders (SUDs) may play a role in the susceptibility for respiratory infections and disease, including coronavirus 2019 (COVID-2019). However, causal inference is challenging due to comorbid substance use. Methods Using genome-wide association study data of European ancestry (data from >1.7 million individuals), we performed single-variable and multivariable Mendelian randomization to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…This reduction in causal effects might reflect greater precision in the GCP estimate or an increase in heterogeneity across the samples in the latest COVID-19 GWAS (e.g., of cases with varying degrees of illness severity). Nonetheless, the current non-significant causal results are consistent with another pre-print that utilized traditional Mendelian Randomization methods ( 29 ).…”
Section: Discussionsupporting
confidence: 84%
“…This reduction in causal effects might reflect greater precision in the GCP estimate or an increase in heterogeneity across the samples in the latest COVID-19 GWAS (e.g., of cases with varying degrees of illness severity). Nonetheless, the current non-significant causal results are consistent with another pre-print that utilized traditional Mendelian Randomization methods ( 29 ).…”
Section: Discussionsupporting
confidence: 84%
“…Although tobacco smoking has long been known to increase susceptibility and severity of respiratory viral infection [5,6], the effect of cannabis smoke on the pulmonary antiviral response remains poorly understood. There is some evidence that cannabis users report increased incidence of respiratory symptoms associated with bronchitis and pneumonia [7,8] as well as increased rates of hospitalization and length of stay during respiratory infection compared to non-smokers [9,10]. Furthermore, clinical studies of HIV+ men have shown that cannabis smoke exposure worsened respiratory infections [11][12][13] and one multivariate Mendelian randomization study found that cannabis use disorder was associated with increased risk of chronic lower respiratory infections and asthma-related infections in the general population [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that cannabis users report increased incidence of respiratory symptoms associated with bronchitis and pneumonia [7,8] as well as increased rates of hospitalization and length of stay during respiratory infection compared to non-smokers [9,10]. Furthermore, clinical studies of HIV+ men have shown that cannabis smoke exposure worsened respiratory infections [11][12][13] and one multivariate Mendelian randomization study found that cannabis use disorder was associated with increased risk of chronic lower respiratory infections and asthma-related infections in the general population [10]. Therefore, in the wake of widespread legalization, it is crucial that we understand to what extent cannabis smoking might impact the pulmonary host-defense mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, obesity is associated with the risk of hospitalization and mortality due to COVID-19 [ 3 , 5 ]. Behavioral risk factors have also been found to be associated with COVID-19 outcomes, above all in some regions where the prevalence of tobacco and alcohol use is high [ 7 ]. A systematic review suggested that smokers appear to be at a low risk of SARS-CoV-2 infection, while former smokers appear to be at increased risk of hospitalization, increased disease severity, and mortality from COVID-19 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%